Tinjauan Istihsan Terhadap Bai’ al- Wafa’ Di Baitul Maal Wa Tamwil Sidogiri Cabang Bondowoso - Ubaidillah Ubaidillah (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2018)
The birth of the first sharia bank in Indonesia is PT Bank Muamalat Indonesia (BMI). However, lately many emerging sharia-based financial institutions other, cultivated sharia cooperative in the form of BMT. Inside the BMT, we are familiar with the term buy back or bai' al-wafa'. Bai 'al-wafa' is a buying and selling is done by someone who need money by selling (real estate/real property) goods is owned by agreement if he can pay (the price) then he can take back the goods while the legal basis bai 'al-wafa' according to Hanafi Madzhab is istihsan. Istihsan is the turning of a mujtahid from qiyas street jaly (real) to qiyas the khafi (vague) or the turning of a mujtahid from law kulli (general) to the law istitsna`i (limit) because it crossed their minds there is a superior proposition.